Perspectives in Performing Arts Medicine Practice : a Multidisciplinary Approach - Lee, Sang-Hie; Morris, Merry Lynn; Nicosia, Santo V. (Springer, 2020)
Performing Arts Medicine (PAM) is a growing area of specialization within the performing arts field, which addresses the multi-faceted health and wellness of performing artists. This sub-discipline within performing arts is interdisciplinary in nature, involving the expertise of performing arts educators and researchers, physicians and other health professionals. This first of its kind text appeals to a very wide audience that includes performing arts clinical practitioners and health science researchers as well as performing arts pedagogues and performing arts students. The first part of the text gives the reader an overview of the field and discusses over-arching themes and issues in PAM. Part two presents an array of music and dance research involving primarily case studies that address significant issues of concern for performing artists and have implications for pedagogical practice. Part three provides research-based perspectives derived from professionals sharing their in-practice experiences. Finally, part four describes useful PAM models of implementation supporting the needs of performing artists in different settings. Written by experts in the field, Perspectives in Performing Arts Medicine Practice is a valuable resource for performing arts physicians, educators and researchers.